Applicability of Competency-Based Assessment for TVET Interns: Comparing Between Indonesia and Laos - Ana, Ana; Widiaty, Isma; Murniati, Dewi Eka; Phommavong, Deauansavanh; S, Saripudin; Grosch, & Michael (Journal of Technical Education and Training, 2019)
This study is an international research collaboration of RAVTE (The Regional Association for Vocational Teacher Education in East and Southeast Asia) members which analyses the assessment of students’ internship using Competency-Based Assessment (CBA) approach. This study analyses the application of CBA for internship assessment using four relevant CBA subcategories: 1) Standards, 2) Planning, 3) Methods, 4) Evidence and, Judgment. The study aims to take a portrait of CBA application in selected three universities, two in Indonesia and one in Laos. The research used a descriptive quantitative approach which conducted among 85 samples. The results give an understanding on the suitability of CBA implementation in each country and to identify potential obstacles. The study revealed that respondents from both countries were quite successful in using evidence and judgement for CBA. However, there were differences in the performance of internships assessment. Most respondents at the two universities use the CBA standards for their internships programs. While the Indonesian samples are successful at applying CBA principles of planning (89.39%), the surveyed respondents from Laos still seemed to have more difficulties in this area (61,2%). While the Indonesian universities rated good in using methods to assess the application in the internship industry (78%), it was found that the methods used for assessing students’ internship at the university in Laos was less satisfying (35.5%). Some issues identified includes unclear guidance of competencies identification unit, lack of mechanism for coordination between quality assurance institutions, and a very limited access for industry collaboration and participation in the assessment planning, standard, method, and judgment.